RHYMED HISTORICAL TEXTS: BIBLIOGRAPHY OF GEORGIAN MANUSCRIPTS - Маджарашвили, Георгий Тамазович (History, Archeology and Ethnography of the Caucasus, 2023)
Historical fiction and rhymed history are two distinct genres of literature that deal with historical events and characters, but their approaches to history are different. Rhymed history, as a type ofpoetry, presents historical events in verse form, prioritizing historical accuracy, while in historical fiction, the story itself is fictional, with invented characters, events and scenarios. Georgian literature contains many poetic works of various genres, including rhymed historical texts. Rhymed history was widespread in Georgia, especially from the 18th century. The poetic form makes historical events more memorable. As a result, rhymed history was used to teach children. These texts are typically written in ballad form and usually include simplified versions of historical events. Rhymed history represents a transitional stage between literature and folklore. It is not easy to find rhymed historical texts in catalogues of Georgian manuscripts. Thus, we decided to prepare this work. A bibliography of Georgian rhymed historical texts is published for the first time.
Keywords: Georgia; Caucasus; Historical Sources; Ancient World History; Medieval History; New history; Georgian Literature